In Situ Calls Of The Marine Perciform Glaucosoma Hebraicum - Parsons, Miles; Longbottom, Simon; McCauley, Robert; Lewis, P.; Fairclough, D. (Australian Acoustical Society, 2014)
West Australian dhufish (Glaucosoma hebraicum), a marine perciform, possess a swim bladder which has associated muscles that are used in sound production. Individuals have been recorded producing sounds during capture that may be associated with disturbance from their normal behaviour. To determine whether individuals produce sound during natural behaviour, a passive sea-noise logger was deployed on the seafloor for one month in close proximity to low-relief artificialsubstrates occupied by G. hebraicum. During this time, both juvenile and sub-adult G. hebraicum were observed within metres of the logger on numerous occasions. At approximately the same time, sounds with characteristics similar to the disturbance calls of G. hebraicum were detected by the logger. Two types of swimbladder generated calls were recorded, one of widely-spaced pulses and the other of pulses in quick succession The maximum received levels and sound exposurelevels of the recorded calls were 132 dB re 1 μPa and 121 dB re 1 μPa2.s, respectively. Based on previously determined G. hebraicum source levels and time of arrival techniques (direct and surface-reflected ray paths), the vocalising fish were estimated at between 1 and 19.5 m from the hydrophone and thus within the area where they had been observed. This study has provided evidence that juvenile G. hebraicum produce sounds at similar source levels to those generated during human induced disturbance. This indicates that sound is produced by individuals of this species during normal behaviour, but may or may not be associated with natural sources of disturbance.